The necessary incorporation of the community pharmacist to the interdisciplinary team that assists the terminally ill patient - Ibáñez del Pino, Rafael (2021)
This work starts from the recognition of the important role that the community pharmacist plays, in health care, to people who suffer from a terminal process and to their family members and / or caregivers. There is no doubt that the advice, treatment and accompaniment of health professionals is essential in any pathology that involves a vital commitment. The community pharmacist, as a health agent, must be involved in these processes. However, on many occasions it is forgotten by a health system that wastes, in this way, one of its most qualified professionals. We are convinced that the terminally ill patient and their family members and / or caregivers would be greatly favored by a greater involvement of pharmacists in their processes. For this reason, this article reflects on the benefits of including the community pharmacist in the healthcare team that cares for people in the terminal phase.